If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(m + 6) = 4 Reorder the terms: 4(6 + m) = 4 (6 * 4 + m * 4) = 4 (24 + 4m) = 4 Solving 24 + 4m = 4 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 4m = 4 + -24 Combine like terms: 24 + -24 = 0 0 + 4m = 4 + -24 4m = 4 + -24 Combine like terms: 4 + -24 = -20 4m = -20 Divide each side by '4'. m = -5 Simplifying m = -5
| 3x-12+3=33 | | 63=9m | | 2h+4h-9h=h | | a-11=-18 | | 10x-4x-2-1=15 | | 4[1-(-6x-2)]=120x+44 | | 4[1-(6x-2)]=120x+44 | | 5x-(2x-1)=10+2(3-x) | | 3x^2-5=34 | | -.4=g-4.9 | | -5x-6+9x=34 | | 2x^2+3+5x=0 | | 5(b-6)=90 | | -5(x+9)-7=-52 | | 4x^2+5y^2-20=0 | | 6(3y-7)=56 | | 176576=2x+29888 | | 4x+4y+2-2y-7x-6= | | 13y-11y=8 | | x^2+3+5x=0 | | 7x^2-16x+100=0 | | 8y-25=13-11y | | 8k-3+5=-40 | | x^3+4+2x=0 | | 8k-3+5=40 | | R=4x+18x | | X-y^4+9y^2=0 | | 5/3=x+3 | | 0.25n+10=0.666n | | x^2+2+3x=0 | | 10x^3-15x^2-4x+6= | | 8(k-9)=40 |